2000
DOI: 10.1161/01.hyp.35.2.555
|View full text |Cite
|
Sign up to set email alerts
|

β-2 Adrenergic Receptor Gene Variations, Blood Pressure, and Heart Size in Normal Twins

Abstract: Abstract-Genetic variability, which influences cardiovascular phenotypes in normal persons, is likely to be relevant to cardiovascular disease. We studied normal monozygotic and dizygotic twins and found strong genetic influences on blood pressure and heart size. We then relied on the dizygotic twins and their parents to apply molecular genetic techniques. We performed a linkage analysis with markers close to the ␤-2 adrenergic receptor (AR) gene locus in the dizygotic twins and their parents and found strong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(62 citation statements)
references
References 31 publications
6
56
0
Order By: Relevance
“…In studies of quantitative traits the Gly allele carriers had increased systolic blood pressure and the Glu allele carriers of the Gln27Glu variant had an increase in systolic blood pressure. These associations were weak and when considering adjustment for multiple testing these associations become insignificant; however, both observations are consistent with earlier findings [10,15].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In studies of quantitative traits the Gly allele carriers had increased systolic blood pressure and the Glu allele carriers of the Gln27Glu variant had an increase in systolic blood pressure. These associations were weak and when considering adjustment for multiple testing these associations become insignificant; however, both observations are consistent with earlier findings [10,15].…”
Section: Discussionsupporting
confidence: 91%
“…The same ambiguity is observed when the two variants are examined in relation to hypertension [9,10,[12][13][14][15] and type 2 diabetes [2,5,9,14,[16][17][18].…”
Section: Introductionmentioning
confidence: 88%
“…The β2AR polymorphisms accounted for ∼2% of the observed variation in blood pressure (Bray et al 2000). While results of some groups confirmed the association between the 16Gly allele and blood pressure (Kotanko et al 1997;Rosmond et al 2000;Gratze et al 1999), others found opposite effects, i.e., an association between the 16Arg allele and hypertension (Busjahn et al 2000;Bengtsson et al 2001a,b;Timmermann et al 1998) or no effects at all (Herrmann et al 2002;Kato et al 2001;Xie et al 2000; for a recent meta-analysis see Hahntow et al 2006). Again, differing inclusion of haplotypes, variations in ethnicities and different study designs may contribute to these sobering results.…”
Section: Genetic Variants In β-Adrenoceptor Genesmentioning
confidence: 98%
“…A study in normotensive twins indicated that all three polymorphisms might be associated with ventricular wall thickness. 92 However, other studies have failed to detect any association between the Arg16Gly and Gln27Glu polymorphisms and cardiac dimensions. [95][96][97] These studies did not investigate the role of the Thr164Ile variant.…”
Section: ␤ 1 -Adrenergic Receptor Polymorphismsmentioning
confidence: 98%
“…90 There is marked linkage disequilibrium between these two polymorphisms. 92 The Gly16 receptor displays enhanced agonist-promoted downregulation, whereas the Glu27 form is resistant to downregulation. 90,93 Two studies have investigated the effect of ␤ 2 -adrenergic polymorphisms in heart failure.…”
Section: ␤ 1 -Adrenergic Receptor Polymorphismsmentioning
confidence: 99%